1-(2-Hydroxyethyl)-3-phenylthiourea - Abdelhamid, Antar A. (International Union of Crystallography, 2012)
The title compound, C(9)H(12)N(2)OS, was obtained unexpectedly in a multicomponent reaction of an equimolar ratio of phenyl isothiocyanate, malononitrile and aminoethanol. The –C(H(2))–N(H)–(C=S)–N(H)– methylthiourea–methane group is almost normal to the phenyl ring, with a dihedral angle of 71.13 (9)°. The N—C—C—O torsion angle is 72.8 (2)°. In the crystal, molecules are connected by N—H⋯O, O—H⋯S and N—H⋯O hydrogen bonds, forming a three-dimensional network.